2020
DOI: 10.1002/pbc.28294
|View full text |Cite
|
Sign up to set email alerts
|

The role of magnetic resonance imaging in the diagnosis of central nervous system involvement in children with acute lymphoblastic leukemia

Abstract: Purpose Acute lymphoblastic leukemia (ALL) is the most frequent malignancy in childhood. As central nervous system (CNS) involvement requires an intensified CNS‐targeted therapy, timely diagnosis is essential. The aim of this retrospective analysis was to evaluate whether cranial magnetic resonance imaging (MRI) examinations findings correlate with cerebrospinal fluid (CSF) analysis on CNS involvement and whether MRI examinations reveal incidental findings with a clinical consequence. Methods All pediatric pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…In particular, cases with NM tended to be older. This is consistent with literature reports [ 4 , 24 , 25 ]. Age, but not sex, significantly associated with NM, where the group within the range of 6 to 12 years old was more affected.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In particular, cases with NM tended to be older. This is consistent with literature reports [ 4 , 24 , 25 ]. Age, but not sex, significantly associated with NM, where the group within the range of 6 to 12 years old was more affected.…”
Section: Discussionsupporting
confidence: 94%
“…Conversely, this NM is within the first places in other reports [ 35 ]. In this study, PRES may had been underdiagnosed because all children had a head CT scan but not all had Magnetic Resonance Imaging (MRI), which depended on the medical criteria of each assigned physician, which was different from the recommended MRI for all children with leukemia showing NM [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of AL of the CNS in human medicine requires a combination of clinical signs, CSF cytospin, +/− flow cytometry, +/− MRI, and specific cases of meningeal/tissue biopsy ( 24 , 27 , 29 , 30 , 32 ). A focal or diffuse nodular leptomeningeal enhancement and enlargement of the cranial nerves on MRI are considered indicative of CNS involvement and warrant local treatment ( 33 , 34 ). Pachymeningeal enhancement at two or more sites in the brain is a negative prognostic factor ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…The MRI scan is of particular relevance in patients with AL and normal CSF analysis but with a high clinical suspicion of CNS involvement ( 33 ). Historically, the diagnosis of leukemia of the CNS relied mainly on the cytospin of the CSF.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have reported that routine MRI examination as initial work-up does not add any information regarding treatment of children with ALL nor does it improve the detection of CNS involvement compared with CSF analysis alone. These data resulted in a change of our internal standard [ 17 ]. Similarly, our present data demonstrate that EEG findings during initial work-up are not helpful in predicting neurological complications during therapy for ALL.…”
Section: Discussionmentioning
confidence: 99%